2017
DOI: 10.1080/24694193.2017.1386967
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Distraction (Cartoon-Patterned Clothes and Bubble-Blowing) on Pain and Anxiety in Preschool Children during Venipuncture in the Emergency Department

Abstract: In preschool children, venipuncture is considered a bodily threat that can cause pain and anxiety, as well as being a traumatic experience. If the pain and anxiety felt by a child during a venipuncture is not addressed properly, it can result in a traumatic experience, and traumatic events in childhood can have long-term consequences. Atraumatic treatment in the emergency department has been little explored in previous research; therefore, the present study assessed the effectiveness of using the distractions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 11 publications
0
15
0
2
Order By: Relevance
“… 20 This finding is consistent with that of a study conducted on 57 pre-school children who were subjected to a distraction involving blowing bubbles during venipuncture; the study reported lower pain levels in these children during the procedure. 10 …”
Section: Discussionmentioning
confidence: 99%
“… 20 This finding is consistent with that of a study conducted on 57 pre-school children who were subjected to a distraction involving blowing bubbles during venipuncture; the study reported lower pain levels in these children during the procedure. 10 …”
Section: Discussionmentioning
confidence: 99%
“…65 Most of the published clinical trials on cognitive and behavioral strategies conducted in the ED setting used some form of distraction. [66][67][68][69][70][71][72][73][74][75][76][77] The most commonly reported procedures were venipuncture and laceration repair. All except 2 66,77 of these studies reported some degree of improved observed pain/distress (by parents or observers) or self-reported pain with intervention.…”
Section: Local Nerve Blocksmentioning
confidence: 99%
“…Most of the published clinical trials on cognitive and behavioral strategies conducted in the ED setting used some form of distraction 66–77 . The most commonly reported procedures were venipuncture and laceration repair.…”
Section: Introductionmentioning
confidence: 99%
“…Fungsi gambar motif kartun yaitu untuk hiburan, terkandung juga fungsi informatif, maupun edukatif bahkan persuasif. Manfaat kartun bagi anak-anak yaitu: sebagai hiburan, melatih daya tangkap anak, menanamkan nilai-nilai dan melatih kreatifitas anak (7). Adapun tujuan dari penelitian ini untuk mengetahui pengaruh teknik distraksi penggunaan rompi motif kartun terhadap perilaku kecemasan pada anak usia pra sekolah di Rumah Sakit Tk.II Udayana.…”
Section: Pendahuluanunclassified
“…Fungsi gambar motif kartun yaitu untuk hiburan, terkandung juga fungsi informatif, maupun edukatif bahkan persuasif. Manfaat kartun bagi anak-anak yaitu: sebagai hiburan, melatih daya tangkap anak, menanamkan nilai-nilai dan melatih kreatifitas anak (7).…”
Section: Pendahuluanunclassified